PERBEDAAN KADAR FLUOR PADA AIR SUMUR GALI SEBELUM DAN SESUDAH PROSES KOAGULASI FLOKULASI KAPUR DAN TAWAS - Soerahman, Moh; Rusmiati, Rusmiati; P. Irawan, H. Djoko Windu (Widya Warta, 2012)
Levels of Fluorine (F) greater than 1.5 mg/l can cause stomach ailments, bone loss and brown enamel, fluorosis, liver damage, kidney damage and bone fragility (osteoporosis). This study aimed to perform the processing of fluorine with the coagulation, flocculation, and adsorption systems, so as to minimize the levels of fluoride in the water. The methods of coagulation and flocculation made use of lime (5%) and alum (5%), with rapid stirring variation 5, 10, 15 minutes and slow stirring 3 minutes at a pH adjusted to 8 and looping treatments (replication) of each 6 times for every 500 ml of water processed. Dug well water in Bantal Village, District of Asembagus, Situbondo, East Java, has a value of pH = 6.6 with a high fluorine concentration = 1.93 mg/l. Fluorine processing technology with the coagulation and flocculation systemsÂ  for lime and alum is strongly influenced by the dose of pH and alum. Precipitation using alum achieves maximum results at pH = 8.1 with a dose of 5% lime and alum dose of approximately 5 ml of 5% in the ratio 1 : 4 and the deposition time = 60 minutes. In these conditions about 1.63 mg/l (83.93%) fluorine content of dug well water decreases from initial value of 1.93 mg fluoride / l to 0:31 mg/l. There are varying levels of fluorine (F) dug well water samples before and after coagulation and flocculation processes of lime and alum. Rapid stirring = 5 minutes can reduce the average fluorine content of 1.39 mg/l (72.53%), rapid stirring = 10 minutes can reduce the average fluorine content of 1.57 mg/l (80.82%) and rapid stirring = 15 minutes can reduce the average fluorine content of 1.63 mg/l (83.93%). Further research needs to be done by varying the addition of alum to reduce the dose volume of fluorine up to the limit allowed by the Minister Regulation. 416/Menkes/Per/IX/1990 of these Terms and monitoring of water quality = 1.5 mg/l.